EFFECT OF OLEORESIN HEAT TREATMENT ON MECHANICAL AND PHYSICAL PROPERTIES OF THE BAMBOO Thyrsostachys siamensis - Thi Kim Hong, Tang; Nhat Quang, Nguyen (Journal of Forestry Science and Technology, 2021)
In this study, Thyrsostachys siamensis was treated oleoresin heat under different temperatures (120oC to 140oC) and durations (60 min to 120 min). The oleoresin used in this study is extracted from Dipterocarpus alatus. Response surface methodology (RSM) models for treatment temperature and treatment duration of oleoresin heat treated T. siamensis were developed. T. siamensis samples were treated oleoresin heat with different treatment temperatures (116oC to 145oC) and times (48 min to 133 min). The water absorption (WA), thickness swelling (TS), anti-swelling efficiency (ASE), modulus of rupture (MOR) and modulus of elasticity (MOE) of the treated samples were determined. The results are demonstrated that the dimensional stability of T. siamensis was enhanced by oleoresin heat treatment and improved along with increasing temperature. However, there was a reduction in strength properties as shown by decreased MOR and MOE. The proper temperature and time applied at 140oC for 60 min resulting the WA 28.65%, TS 3.23%, MOR 160.26 MPa and MOE 5.07 GPa. Better dimensional stability could be observed in the samples treated at higher temperature even when exposed to a shorter time. Applying an optimal treatment condition of the temperature 140oC for 120 min, the ASE achieve a high value of 50.8%.